KARAKTERISTIK IBU HAMIL TRIMESTER I YANG MENGALAMI MUAL MUNTAH DI BPM NI WAYAN SURI, SKM, SST TAHUN 2018 - Dewianti, Ni Made (Jurnal Genta Kebidanan, 2018)
Nausea vomiting in pregnancy is called morning sickness, experienced by about 70-80% of pregnant women and is a phenomenon that often occurs at 5-12 weeks of gestation. This study aims to determine the characteristics of pregnant women who experience nausea and vomiting. This research method is descriptive. The population in this study were pregnant women who made antenatal visits at BPM Ni Wayan Suri, SKM, S.ST in 2018 with purposive sampling technique. The sample in this study were first trimester pregnant women who experienced nausea and vomiting and included inclusion criteria in BPM Ni Wayan Suri, SKM, S.ST. Data were analyzed by descriptive analysis to determine the incidence of nausea and vomiting in pregnant women in the first trimester and the characteristics of pregnant women who experienced nausea and vomiting. The results obtained from this study were the frequency of nausea and vomiting in pregnant women in the first trimester found that most of them were 17 people (56.6% ) The average nausea and vomiting of pregnant women in the first trimester is 8. The characteristics of pregnant women who experience nausea and vomiting are the majority of respondents, namely 21 people (70%) in the age category of young adults, almost half of the respondents are 13 people (43.3%) with secondary education, most of the respondents are 16 people (53.3%) work, and most respondents were 19 people (63.3%) primigravida.Mual muntah pada kehamilan disebut dengan morning sickness, dialami oleh sekitar 70-80% wanita hamil dan merupakan fenomena yang sering terjadi pada umur kehamilan 5-12 minggu. Penelitian ini bertujuan untuk mengetahui karakteristik ibu hamil yang mengalami mual muntah. Metode penelitian ini adalah deskriptif. Populasi dalam penelitian ini adalah ibu hamil yang melakukan kunjungan antenatal di BPM Ni Wayan Suri, SKM, S.ST Tahun 2018 dengan teknik sampling purposive sampling. Sampel adalah ibu hamil trimester I yang mengalami mual muntah dan memenuri kriteria inklusi. Data dianalisis dengan analisis deskriptif. Hasil penelitian ini adalah sebagian besar yaitu 17 orang (56,6%) mengalami mual muntah pada kategori sedang. Rata – rata mual muntah ibu hamil trimester I yaitu 8,1. Karakteristik ibu hamil yang mengalami mual muntah adalah sebagian besar responden 21 orang (70%) kategori umur Dewasa muda, hampir setengahnya responden yaitu 13 orang (43,3%) berpendidikan menengah, sebagian besar responden yaitu 16 orang (53,3%) bekerja, dan sebagian besar responden yaitu 19 orang (63,3%) primigravida